Abstract Paintings and Nepali Context (SIRJANĀ – A Journal Of Arts and Art Education, 2022)
Abstract art as discussed in this essay covers a period of time that spans about sixty years. The introduction of the abstract art in Nepal marks a certain opening in both art education and practice among the artists. The initial challenge of the abstract art was to make it a familiar subject both among the art lovers as well as among those who respected art but were not able to appreciate it fully. A challenging period came when artists began to work towards making abstract art an acceptable and a very useful artistic practice. The tension between skill of the artists and the indifference of the public is a universal problem. But now the gap is being narrowed down everywhere. The concept of abstract art in Nepal comes from education in schools in Europe and India in the initial phase and later in Nepal itself where art pedagogy became a norm in different art schools and colleges. But artists freely made their paintings abstractas the commonly accepted mode of art. Artists of different generations execute abstract paintings without being critical or interpretative about it. But now things are changing in Nepal. New generation artists who are oriented to the abstract and free forms of art are working to develop a system by putting together the art education, practice and very importantly, the level of public acceptance for that. We should carefully review the history and the present status of that. We should also make the art works 'desirable'. The other important character of Nepali abstract painting is that the artists always work in the contact zones of the representational and the expressionist features. I have interpreted that meeting point as a contact zone. This article attempts to give examples of that dynamic process. Nepali abstract paintings mark a new mode of artistic dynamism in Nepal.